Assessment of the Impact of Insecurity on Women's Entrepreneurial Activities in Shiroro Local Government Area of Niger State - Mshelia, Isma'il, Husain; Salami, Usman, Jeffrey; Otakey, Abbas, Hassan (My University, 2022)
This study examined the impact of insecurity on the entrepreneurial activities of women in Shiroro Local Government Area of Niger State, focusing specifically on issues about women’s financial dependence, the kind of entrepreneurial activities common among them and the dimension of the impact of insecurity on their entrepreneurial endeavours. A sample of 377 women was surveyed, leading to the findings that women in Shiroro are highly entrepreneurial with high level of financial independence, engaging mostly in SMEs. The study also found that while insecurity has an adverse effect on women’s entrepreneurial activities in the form of loss of or decline of capital among other things, the number of women entrepreneurs has not experienced a significant decline. The study recommended that sustainable programmes to improve women’s access to and use of financial services should be created and community policing organisations should also be created and strengthened to combat insecurity in the study area.
Keywords: Banditry; Crime; Entrepreneurship; Insecurity; Shiroro; Women